AI-Driven Diagnostic Imaging: Enhancing Early Cancer Detection through Deep Learning Models - Ariyanto, Danang; Chai, Napat; Krit, Pong (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
Early detection is critical for improving cancer survival rates, yet the interpretation of diagnostic images is subject to human error and variability. Artificial intelligence (AI), specifically deep learning, presents a transformative opportunity to enhance diagnostic accuracy and speed. This study aimed to develop and validate a deep learning model to improve the accuracy and efficiency of early-stage cancer detection in radiological images compared to human expert interpretation. A convolutional neural network (CNN) was trained and validated on a curated dataset of over 20,000 mammography images. The model's diagnostic performance was rigorously evaluated using key metrics, including accuracy, sensitivity, specificity, and the area under the receiver operating characteristic curve (AUC), against a biopsy-verified ground truth. The AI model achieved an overall accuracy of 97.2%, with a sensitivity of 98.1% and a specificity of 96.5%. The model's performance, with an AUC of 0.98, was comparable to that of senior radiologists and significantly reduced false-negative rates. AI-driven deep learning models are highly effective and reliable tools for augmenting diagnostic imaging. They can significantly enhance early cancer detection, reduce diagnostic errors, and serve as a powerful assistive tool for radiologists in clinical practice.